2015
DOI: 10.1016/j.neuron.2015.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Seizing upon Mechanisms for Impaired Consciousness

Abstract: Summary Transient loss of consciousness experienced during, and shortly after, focal temporal lobe seizures is a complex phenomenon with life threatening repercussions for persons with epilepsy. In this issue of Neuron, Motelow et al. (2015) describe the first evidence for decreased cholinergic drive and depressed subcortical arousal in seizures as a novel mechanism for impaired cortical function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…We do not know whether PI is related solely to decreased postictal arousal or whether there is also additional impairment of cortical and subcortical motor circuits independent of impaired arousal. During seizures there is decreased cholinergic transmission from subcortical arousal structures to the thalamus and frontal cortex with slow wave activity and decreased metabolism of frontal cortex . Activation of subcortical arousal systems by stimulation of intralaminar nuclei following a seizure resulted in increased EEG desynchronization and resumption of exploratory behaviors …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not know whether PI is related solely to decreased postictal arousal or whether there is also additional impairment of cortical and subcortical motor circuits independent of impaired arousal. During seizures there is decreased cholinergic transmission from subcortical arousal structures to the thalamus and frontal cortex with slow wave activity and decreased metabolism of frontal cortex . Activation of subcortical arousal systems by stimulation of intralaminar nuclei following a seizure resulted in increased EEG desynchronization and resumption of exploratory behaviors …”
Section: Discussionmentioning
confidence: 99%
“…During seizures there is decreased cholinergic transmission from subcortical arousal structures to the thalamus and frontal cortex with slow wave activity and decreased metabolism of frontal cortex. 22,23 Activation of subcortical arousal systems by stimulation of intralaminar nuclei following a seizure resulted in increased EEG desynchronization and resumption of exploratory behaviors. 24 We propose that the following sequence may be important in SUDEP.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Moreover, unlike cholinergic neurones, glutamatergic neurones of the PPN have not been demonstrated to exhibit decreased firing during seizures. 70,71 Furthermore, recent evidence has indicated that the fast glutamatergic/GABAergic system is the backbone for arousal networks, while the cholinergic and monoaminergic system plays a modulatory role. 27,28 These findings warrant future studies elucidating the role of different neurotransmitter systems on the PVIN/PC dynamic pertinent to cognition, consciousness, and epilepsy.…”
Section: Cognition Consciousness and Epilepsymentioning
confidence: 99%
“…However, the relationship between PGES and respiratory dysfunction can also point towards the presence of some common pathophysiological mechanisms, involving seizure‐activated cortical and subcortical inhibitory networks. A theoretical role of other circuits has been proposed but not proven: in particular seizure‐related dysfunction of the 5‐HT and glutamatergic systems, with inhibition of the subcortical arousal system and consequent impaired consciousness and motionlessness (Kinney and Thach, 2009; Kothare and Singh, 2014), and decreased cholinergic transmission from subcortical arousal structures to the thalamus and frontal cortex with possible involvement of motor circuits (Farzampour and Huguenard, 2015; Motelow et al ., 2015).…”
Section: Post‐ictal Immobilitymentioning
confidence: 99%